Life well spent: four decades in the Indian foreign service - Chandra, Satish (New Delhi Rupa, 2023)
The book is enriched with fascinating vignettes of some of the countries to which the author was assigned and their relations with India. Some of the major issues touched upon include the Soviet invasion of Czechoslovakia in 1968, developments in Pakistan in the lead-up to the 1971 conflict, Indias recognition of Western Sahara, defusing IndiaPakistan tensions consequent upon Operation Brass Tacks,, the initiation of the IndiaPakistan composite dialogue process, Blunting Pakistans anti-India jihad in the UN Commission on Human Rights in 19934, disarmament negotiations pertaining to CTBT and FMCT, the Kargil conflict, the setting up of the National Security Council system and security reform in India.
Keywords: Security and Foreign Affairs Sector; Indian Foreign Service; IFS as an author